Corrugated web plate girders - Leamer, Derek (Kansas State University, 2023)
Built-up plate girders are typically used in construction when there are large loads and long span that rolled shapes do not work. The high web slenderness ratio makes plate girders susceptible to buckling among other limit states. Transverse stiffeners are often required along the span of the girder to prevent local buckling. The use of a corrugated web eliminates the need for transverse stiffeners, which reduces fabrication cost significantly. The flexural and shear behaviors of Corrugated Web Plate Girders are different from regular plate girders due to its unique web geometry. Various web geometries are available with further research developing design equations for each. The web introduces a transverse moment that the flanges must resist in addition to in-plane loads. Design equations are used in Europe through Eurocode. Researchers have proposed equations for use in North America with similar assumptions as those in Europe, however they are not adopted yet in design code. This report seeks to introduce design methods and practice of corrugated web plate girders in Europe as well as proposed North American design methods.
Keywords: Corrugated web plate girders; Steel; Plate girders